Hubungan Antara Tingkat Self Awarenss dengan Perencanaan Karir pada Siswa Kelas IX di SMP Negeri 16 Singkawang - Tri Handayani; Insan Suwanto; Kamaruddin Kamaruddin (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to: (1) determine the level of self-awareness among ninth-grade students at SMP Negeri 16 Singkawang; (2) determine the career planning of ninth-grade students at SMP Negeri 16 Singkawang; (3) find out whether there is a significant relationship between self-awareness and career planning among ninth-grade students at SMP Negeri 16 Singkawang. This research employs a quantitative approach with a causal associative research design. The population of this study consisted of 128 ninth-grade students at SMP Negeri 16 Singkawang, with a sample of 56 students selected using a simple random sampling technique. Data collection was carried out using measurement techniques with data collection instruments in the form of self-awareness and career planning questionnaires. The data analysis technique used was statistical analysis and Pearson product-moment correlation. The results of data analysis show that: (1) the level of self-awareness among ninth-grade students at SMP Negeri 16 Singkawang is in the high category (79%); (2) the level of career planning among ninth-grade students at SMP Negeri 16 Singkawang is in the high category (69%); (3) there is a relationship between the self-awareness variable and the career planning variable, with a low degree of correlation (correlation coefficient = 0.367), and the relationship is positive. A positive relationship means that the higher or better the self-awareness variable, the higher or better the career planning variable, and vice versa, the lower the self-awareness variable, the lower the career planning variable.